2016
DOI: 10.4329/wjr.v8.i2.148
|View full text |Cite
|
Sign up to set email alerts
|

Advances in determining abdominal aortic aneurysm size and growth

Abstract: Abdominal aortic aneurysm is a common pathology in the aging population of the developed world which carries a significant mortality in excess of 80% in case of rupture. Aneurysmal disease probably represents the only surgical condition in which size is such a critical determinant of the need for intervention and therefore the ability to accurately and reproducibly record aneurysm size and growth over time is of outmost importance. In the same time that imaging techniques may be limited by intra- and inter-obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…The use of volume measurements in addition to diameter measurements for detection of aneurysm growth has been a topic of interest in multiple vascular territories. Literature on abdominal aortic aneurysms showed that volumetric measurements may be superior to conventional diameter measurements for detecting size changes as a follow-up tool after endovascular repair 14,15 , as well as untreated aneurysm surveillance 16 . In intracranial aneurysms, a moderate correlation of volume and diameter at best was only found in predominantly saccularly shaped aneurysms, and not at all in fusiform aneurysms 17 .…”
Section: Discussionmentioning
confidence: 99%
“…The use of volume measurements in addition to diameter measurements for detection of aneurysm growth has been a topic of interest in multiple vascular territories. Literature on abdominal aortic aneurysms showed that volumetric measurements may be superior to conventional diameter measurements for detecting size changes as a follow-up tool after endovascular repair 14,15 , as well as untreated aneurysm surveillance 16 . In intracranial aneurysms, a moderate correlation of volume and diameter at best was only found in predominantly saccularly shaped aneurysms, and not at all in fusiform aneurysms 17 .…”
Section: Discussionmentioning
confidence: 99%
“…The reason why the 3D method overestimates the volume of polymer is unknown, few studies have discussed the tendency of 3D CT reconstruction to overestimates the size of the aortic aneurysm sac [ 4 ]. It might also be related to the characteristics of the polymer material.…”
Section: Discussionmentioning
confidence: 99%
“…3D reconstruction volume measurements have been documented as a reliable method for tracking abdominal aorta aneurysmal (AAA) growth and tumor necrosis quantification (15, 23). Multiple studies have demonstrated volume measurements are more sensitive to abdominal aortic aneurysm growth change since maximal diameters do not always change with aortic dilatation (2426).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have demonstrated volume measurements are more sensitive to abdominal aortic aneurysm growth change since maximal diameters do not always change with aortic dilatation (2426). Kontopodis et al showed 3D reconstructions from CT scans are more predictive than 2D measurements for determining need for surgical intervention in patients with AAA (23). Uribe et al demonstrated 3D cardiac ventricular volume calculations at MR had less intra- and inter-observer variability than traditional 2D measurements (27).…”
Section: Discussionmentioning
confidence: 99%